INFLATION TARGETING DAN TANTANGAN IMPLEMENTASINYA DI INDONESIA - Munawar Ismail (Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
Inflation targeting is a new and also still challenging model of monetary policy. Nevertheless the number of countries applying this model is continuously increasing. Objectives of the study are (1) to review the meaning and requirements of the inflation targeting, (2) to examine the implementation of inflation targeting in developing countries and (3) to evaluate the application of inflation targeting in Indonesia. As a new approach in goups of monetray policies, the inflation targeting has specific conditions that are not available in monetary targeting and it’s variants. Though structures of most developping countries’ economies do not totally conform to the conditions of inflation targeting, those countries that apply inflation targeting had been succesful in lowering their inflation rate. Yet the implementation of inflation targeting in Indonesia, in the past, was not satisfied either in decreasing the inflation rate or in bringing the actual inflation to the rate of it’s target.